The effect of feed water dissolved organic carbon concentration and composition on organic micropollutant removal and microbial diversity in soil columns simulating river bank filtration. (February 2016) - Bertelkamp, C.; van der Hoek, J.P.; Schoutteten, K.; Hulpiau, L.; Vanhaecke, L.; Vanden Bussche, J.; Cabo, A.J.; Callewaert, C.; Boon, N.; Löwenberg, J.; Singhal, N.; Verliefde, A.R.D.
Abstract: This study investigated organic micropollutant (OMP) biodegradation rates in laboratory-scale soil columns simulating river bank filtration (RBF) processes. The dosed OMP mixture consisted of 11 pharmaceuticals, 6 herbicides, 2 insecticides and 1 solvent. Columns were filled with soil from a RBF site and were fed with four different organic carbon fractions (hydrophilic, hydrophobic, transphilic and river water organic matter (RWOM)). Additionally, the effect of a short-term OMP/dissolved organic carbon (DOC) shock-load (e.g. quadrupling the OMP concentrations and doubling the DOC concentration) on OMP biodegradation rates was investigated to assess the resilience of RBF systems. The results obtained in this study imply that – in contrast to what is observed for managed aquifer recharge systems operating on wastewater effluent - OMP biodegradation rates are not affected by the type of organic carbon fraction fed to the soil column, in case of stable operation. No effect of a short-term DOC shock-load on OMP biodegradation rates between the different organic carbon fractions was observed. This means that the RBF site simulated in this study is resilient towards transient higher DOC concentrations in the river water. However, a temporary OMP shock-load affected OMP biodegradation rates observed for the columns fed with the river water organic matter (RWOM) and the hydrophilic fraction of the river water organic matter. These different biodegradation rates did not correlate with any of the parameters investigated in this study (cellular adenosine triphosphate (cATP), DOC removal, specific ultraviolet absorbance (SUVA), richness/evenness of the soil microbial population or OMP category (hydrophobicity/charge). Graphical abstract: Highlights: RBF is resilient towards variations in the organic carbon fractions. RBF is resilient towards a DOC shock-load. RBF is not resilient towards an OMP shock-load. An OMP shock-load increases OMP biodegradation rates for river water organic matter. An OMP shock-load increases OMP biodegradation rates for hydrophilic organic matter.